Hearing Loss From Multidisciplinary Teamwork to Public Health - Wang, Tang-Chuan (IntechOpen, 2021)
The auditory system is one of the finest structures in the human body. Although its anatomical structure is so small compared to other organs, without it, it would greatly affect a person's basic life. Hearing loss, also known as hearing impairment, is a partial or total inability to hear. When people communicate with others, listening is always the first step. That is why Helen Keller once said, "Blindness separates people from things; deafness separates people from people." To avoid the "epidemic" of hearing loss in the near future, it is necessary to promote early screening, change public attitudes toward noise, and wear hearing aids appropriately. Based on the contributions of many authors, whom I sincerely respect, this book incorporates updated developments as well as future perspectives in the ever-expanding field of hearing loss. This book can also serve as a reference for persons who are involved in this field whether they are clinicians, researchers, or patients.